Influence of pneumococcal conjugate vaccine 13 on upper respiratory tract microbial biodiversity in infants - Samat Kozhakhmetov; Y. Aitenov; Б.А. Рамазанова; Yekaterina Koloskova; Tatyana N Burkutbayeva; Lyazzat Yeraliyeva; Kamilya Mustafina; Gulshakhar Beglarova; Maral Yergazina; Аlmagul Kushugulova (UNS Solo, 2021)
Pneumococcal disease and its associated mortality are burdens on the healthcare system. The intensive introduction of pneumococcal vaccines has provided robust control and infection management worldwide. " "The Pneumococcal Conjugate Vaccine (PCV) has been successfully employed in the national programs of many countries. However, no studies have yet analyzed the effect of pneumococcal vaccines on Central Asian populations. " "We investigated the effect of the pneumococcal vaccine on the nasopharyngeal microbiome of infants under the age of two years. Samples were collected from healthy patients as part of routine hospital check-ups, then subjected to high-throughput sequencing of the V1–V3 region of 16S rRNA for bioinformatics analysis. " "The obtained data were combined with the results of a previously published study (with matching criteria) to increase statistical power. No significant differences were found in vaccination status, sex or age. Nevertheless, the results demonstrated structural changes in the microbiome of the upper respiratory tract under the influence of the PCV13 vaccine. " "The results of beta-diversity unweighted UniFrac distance measuring showed that the experimental groups differed in their qualitative (taxonomic) structure (p < 0.1). In the vaccinated group, the abundance of several symbiotic taxa was significantly decreased, including Streptococcus pneumonia.
Keywords: Pneumococcal conjugate vaccine; Vaccination; Streptococcus pneumoniae; Pneumonia; UniFrac; Medicine; Respiratory tract infections; Biology; Pneumococcal disease; Immunology; Internal medicine; Microbiology; Respiratory system; 16S ribosomal RNA; Antibiotics; Bacteria; Genetics; type of access: open access